2020
DOI: 10.3389/fonc.2020.01172
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: LncRNA DLX6-AS1 Promotes Malignant Phenotype and Lymph Node Metastasis in Prostate Cancer by Inducing LARGE Methylation

Abstract: Long non-coding RNAs (lncRNAs) have recently become recognized as crucial players in cancer cellular events including proliferation, migration, and invasion. Herein, we investigated the potential role of lncRNA DLX6-AS1 in prostate cancer cell malignant behaviors and lymph node metastasis. A differentially expressed lncRNA DLX6-AS1 and its downstream regulatory gene (LARGE) were predicted by analysis in silico. RT-qPCR and western blot analysis results demonstrated that DLX6-AS1 was highly expressed, but LARGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The abnormal expression of lncRNAs have also been reported to contribute to tumorigenic processes of many human malignancies, including PCa 8,9 . In PCa, recent studies have revealed that LncRNA DLX6-AS1 enhances PCa Malignant Phenotype and Lymph Node Metastasis 10 , and LncRNA AC245100.4 promotes the proliferation of PCa through binding to HSP90 11 . Small nucleolar RNA host gene 1(SNHG1), a novel LncRNA, has shown to be aberrantly high expression and oncogenic characteristics in various cancers 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal expression of lncRNAs have also been reported to contribute to tumorigenic processes of many human malignancies, including PCa 8,9 . In PCa, recent studies have revealed that LncRNA DLX6-AS1 enhances PCa Malignant Phenotype and Lymph Node Metastasis 10 , and LncRNA AC245100.4 promotes the proliferation of PCa through binding to HSP90 11 . Small nucleolar RNA host gene 1(SNHG1), a novel LncRNA, has shown to be aberrantly high expression and oncogenic characteristics in various cancers 12 .…”
Section: Introductionmentioning
confidence: 99%
“…7 , 8 For instance, lncRNA DLX6-AS1 contributes to prostate cancer growth and invasion through enhancing LARGE methylation. 9 LncRNA CCAT2 initiates prostate cancer proliferation and metastasis through activation of Wnt signaling. 10 LncRNA LINC00491 promotes lung cancer proliferation, migration and invasion by sponging miR-324 to facilitate SP1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Silencing DLX6-AS1 suppressed the pyroptosis of HK-2 cell through miR-223-3p/NLRP3 signaling in LPS-induced acute kidney injury [ 82 ]. DLX6-AS1 promoted metastasis in prostate cancer via mediating LARGE methylation [ 165 ]. DLX6-AS1 promoted metastasis via miR-641/HOXA9 pathway in osteosarcoma [ 166 ] and targeting miR-577 in esophageal squamous cell carcinoma [ 167 ].…”
Section: Pyroptosis In Cancer Metastasismentioning
confidence: 99%